2019
DOI: 10.1002/jctb.5955
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population dynamics in temperature‐phased anaerobic digestion of municipal wastewater sludge

Abstract: BACKGROUND The present study compared the performance and capability of thermophilic–mesophilic, temperature‐phased anaerobic digestion (TPAD) of wastewater sludge at 45 and 55 °C in terms of rate of hydrolysis and methanogenesis at two point interval times – December and January – with operational conditions kept constant (total solid content 6.5%, solids retention time 12.5 days). RESULTS The reduction of volatile solids (VS) was 77% at 45 °C TPAD‐1 and 72% at 55 °C TPAD‐II. The accumulation of ammonia and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 75 publications
1
8
0
1
Order By: Relevance
“…Lee et al [54] also reported that the accumulation of propionic acid could decrease process performance and lead to process failure. Our results are in agreement with Lee et al [55] who stated that an alarming concentration of propionic acid is 1000-2000 mg/L and suggested that exceeding this limit can inhibit methanogens. In our study, we con rmed that using molasses as a sole substrate in anaerobic digestion, monitoring of propionic acid and total VFA should be determined periodically.…”
Section: Detection Of Vfas Concentrationsupporting
confidence: 93%
See 1 more Smart Citation
“…Lee et al [54] also reported that the accumulation of propionic acid could decrease process performance and lead to process failure. Our results are in agreement with Lee et al [55] who stated that an alarming concentration of propionic acid is 1000-2000 mg/L and suggested that exceeding this limit can inhibit methanogens. In our study, we con rmed that using molasses as a sole substrate in anaerobic digestion, monitoring of propionic acid and total VFA should be determined periodically.…”
Section: Detection Of Vfas Concentrationsupporting
confidence: 93%
“…During this time, in MR35, an unexpected increase in abundance of Beijerinckiaceae from class alpha-proteobacteria and other uncultured bacterium was observed by suppressing the abundance of other families. Hameed et al [55] and Zhang et al [56] identi ed the genera beijerinckia and other related bacteria from the same family in anaerobic communities with stable acetoclastic methanogenesis (74-84%) that shows syntrophic association with methanogens. The bacteria related to family Beijerinkia are known for nitrogen reduction in the anaerobic system [56].…”
Section: Composition Of Bacterial Communitymentioning
confidence: 99%
“…Thus, the microbial diversity and abundance are negatively affected in soils with a pH >7 and high Na + levels (Rath & Rousk, ). Additionally, increased K + could lower bacterial richness and diversity (Hameed et al, ). Different bacterial species show different levels of tolerance to specific ionic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…pH below 6.5 and thermophilic temperature decrease archaea diversity [3,39]. In a study of Hameed et al, the abundance of Methanosarcina-assumed to be a main producer of methane in biogas production-was reduced from 76.7% to 23.8%, and also the alpha diversity decreased with a shift from 35 • C to 55 • C [40]. As a diverse microbiome is assumed to be more stable, staging of AD leads to a better process performance.…”
Section: Microbial Consortia and The Main Products In A Microbial Hydmentioning
confidence: 99%